Shadaqah dalam Perspektif Hadis Nabi - Sulaiman Slamet, Moh. Ibnu (Al-Hikmah, 2011)
The theme of sadaqah in hadith (the Prophet’s traditions) can be grouped into two categories, namely, zakah that is considered as wajib (obligation) and sadaqah that is assumed ordinary Sunnah (tatawwu'). Majority of ulama (Moslem scholars) concluded that sadaqah is an important part in the lives of Moslems. The sadaqah could strengthen horizontal linkages among human beings especially Moslems. In general, Islam considers that from a legal perspective and its funcion sadaqah is priority obligation because not only is an indicator of the truth of one's faith or belief in God as his God and Muhammad as the Messenger of Allah, but also sadaqah if it is managed and utilized in the maximum way it will be able to minimize poverty especially among Moslems